Upaya Meningkatkan Kemampuan Guru dalam Membuat Video Pembelajaran melalui Pelatihan Teknik Mentoring di MAN 1 Gunungkidul - Jauhari Iswahyudi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This action research aims to improve the ability of MAN 1 Gunungkidul teachers in making learning videos. The subjects of the study were teachers at MAN 1 Gunungkidul. This research uses action research methods that are carried out in two cycles, covering the stages of planning, implementation, observation, and reflection. The results of the research and analysis showed: (1) the participants gave a positive response to the implementation of mentoring technique training, feel happy and motivated in completing their tasks, (2) training with mentoring techniques improves teacher understanding in operating powerdirector applications and making learning videos.